Insights into the mechanism and inhibition of fatty acid amide hydrolase from quantum mechanics/molecular mechanics (QM/MM) modelling. (20th March 2009) - Lodola, Alessio; Mor, Marco; Sirirak, Jitnapa; Mulholland, Adrian J.
Abstract : FAAH (fatty acid amide hydrolase) is a promising target for the treatment of several central nervous system and peripheral disorders. Combined QM/MM (quantum mechanics/molecular mechanics) calculations have elucidated the role of its unusual catalytic triad in the hydrolysis of oleamide and oleoylmethyl ester substrates, and have identified the productive inhibitor-binding orientation for the carbamoylating compound URB524. These are potentially crucial insights for designing new covalent inhibitors of this drug target.